The Relationship Between Anxiety and Post-disaster Health Conditions as A Basis for Planning Evidence-Based Psychosocial Intervention in Padang City - Welly, Welly; Harahap, Nurlelasari; Edwin, Vebby Amelia; Husna, Riyana; Putri, Adela Resa; Putra, Deri Andika (Journal of Health Sciences and Epidemiology, 2026)
Natural disasters impose significant psychological and physical burdens on affected communities. Increased post-disaster anxiety can exacerbate overall health conditions and hinder the recovery process, highlighting the need for integrated psychosocial intervention. This study aimed to analyze the relationship between anxiety and post-disaster health conditions among affected communities in Padang City, Indonesia, to provide a basis for evidence-based psychosocial intervention planning in the future. A cross-sectional study was conducted among 115 adults residing in disaster-prone subdistricts. Anxiety was measured using the Generalized Anxiety Disorder-2 (GAD-2) scale, and post-disaster health conditions (focusing on psychological distress and depressive symptoms) were assessed using the Patient Health Questionnaire-2 (PHQ-2). Bivariate analysis was conducted to identify associations with post-disaster health conditions. The results showed that most respondents experienced anxiety (83.5%) and health problems (87.8%). A statistically significant association was found between anxiety and post-disaster health conditions (p = 0.048; OR = 3.45; 95% CI: 1.01–11.8). Anxiety is a significant determinant of post-disaster health conditions among affected communities. These findings reinforce the urgency of anxiety screening as a key component in planning and developing community-based, evidence-based psychosocial interventions during the post-disaster recovery phase.